The effectiveness of the Congo Red Dot paper test in hypertensive disorders of pregnancy: A systematic review and meta-analysis - Khaliq, O. P.; Phoswa, W. N.; Moodley, J. (Frontiers in Reproductive Health, 2023)
Background Congo Red Dot Paper Test (CRDPT) appears to be a simple, cost-effective, non-invasive diagnostic tool for hypertensive disorders of pregnancy (HDP). The main objective of the study is to assess the effectiveness of CRDPT in detecting HDP. Methods This is a systemic review and meta-analysis of published studies on the effectiveness of CRDPT in the detection of HDP. The study was conducted in line with the PRISMA-DTA guidelines. The PICOS framework was used to search for relevant articles using Medline, PubMed, Google Scholar, Web of Science, and the Cochrane Library databases. The articles were screened against a set of inclusion and exclusion criteria and analysed using the Review Manager 5.4 software. Results A title, abstract and full article screening was conducted on 18,153 potential articles based on the inclusion and exclusion criteria. The screening yielded five articles for meta-analysis. The total number of normotensive pregnant women (n = 3,380) in the included studies was five times higher than the total number of women with pre-eclampsia (n = 535). A difference between the HDP and normotensive group was noted. This is indicated by a significantly decreased in the effectiveness of CRDPT in detecting HDP as compared to normotensive group [Risk Ratio (RR) = 6.32 (2.17, 18.43) p < 0.00001]. The included studies had a high nature of heterogeneity (I2 = 98%, p < 0.00001) partially due to different study designs included in the analysis and different regions where studies were conducted given that none of these studies were conducted in African countries where HDP is prominent. Conclusions According to results generated from 5 studies in this meta-analysis, it was found that CRDPT might not be effective in the detection of hypertensive disorder of pregnancy. Moreover, more research, especially in African women where hypertensive disorders of pregnancy are prevalent, are re-quired to ascertain these findings. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021283679, identifier: CRD42021283679.